POSITIONAL AND PHOTOELECTRIC OBSERVATIONS OF CA SIMILAR TO THE OBJECTS SUGGESTED FOR LAUNCHING ACCORDING TO THE ” GLOBAL STAR” PROGRAM - Sheptun, A. D.; Dobrovolsky, A. V.; Paltsev, N. G.; Chaichuk, R. A.; Medvedev, Yu. A.; Petrov, M. P.; Depenchuk, A. E.; Strakhova, S. L.; Naumenko, T. N.; Korniychuk, L. V.; Korobeynikova, E. A. (Одеські астрономічні публікації, 2017)
The given work deals with results of observations of AES being analogues of CA ”Global Star” carried out to study capabilities of interdisposition of satellites suggested for launching according to the ”Global Star” in the zone of their closest approach.